Variaciones sociosemióticas del simbolismo de Sol y Luna entre los pueblos pano* - Moulian Tesmer, Rodrigo (2023)
This article analyzes and contrasts the socio-semiotic modeling patterns of Sun and Moon that encode the denoted meanings and social representations of the principal heavenly bodies among the ethnic groups of the Panoan linguistic family. The study of these symbolic motifs constitutes a way of approaching Panoans’ cultural field that offers insights into its internal configuration and external relations. The research strategyapplied is the case study. The units of analysis are the patterns of primary or linguistic and secondary or discursive modeling of Sun and Moon. The data show linguistic homogeneity but discursive heterogeneity. The registerof representations reveals the coexistence of a diversity of conceptions ofSun and Moon in ontological terms, gender, and relationship modalities assigned to these entities. Within the framework of its system of variants and transformations, two predominant ethnomodels can be distinguished inPanoan groups from certain geographical areas, which present important cross-cultural correlates: Sun as a creator divinity and Moon as an ancestor turned heavenly body. The former is related to the Andean conceptions of Sun, while the latter has been widely recorded in the mythologies of the Amazonian peoples, revealing a system of transductions that inform of its ancient roots.